Pengaruh Penghindaran Pajak dan Risiko Pajak terhadap Nilai Perusahaan Sektor Infrastruktur yang terdaftar di BEI - Santo, Vianty Adella; Sari, Theresia Anggun (Politeknik Ganesha Medan, 2024)
Company value is a reflection of management's efforts in carrying out the company's operational activities. With the high value of the company, it can attract investors to invest their funds in the company. In this research, the influence of company value is seen from tax avoidance and tax risk. Tax avoidance is a legal practice in minimizing tax payments as long as it meets applicable tax regulations. Tax risk is related to the impact if a company carries out tax evasion that does not comply with tax regulations and can result in the imposition of sanctions or fines. The aim of this research is to conduct testing and provide empirical evidence of the influence of the independent variables, namely Tax Avoidance) and Tax Risk on the dependent influence, namely Firm Value with Firm Size as the control variable. This research uses multiple regression analysis and is assisted by the Eviews 9 program. The research results show that tax avoidance and tax risk have no effect on firm value. Firm size has a negative effect on company value.